Maternal Choline Supplementation as a Potential Therapy for Down Syndrome: Assessment of Effects Throughout the Lifespan - Powers, Brian E.; Velazquez, Ramon; Strawderman, Myla S.; Ginsberg, Stephen D.; Mufson, Elliott J.; Strupp, Barbara J. (Frontiers in Aging Neuroscience, 2021)
Maternal choline supplementation (MCS) has emerged as a promising therapy to lessen the cognitive and affective dysfunction associated with Down syndrome (DS). Choline is an essential nutrient, especially important during pregnancy due to its wide-ranging ontogenetic roles. Using the Ts65Dn mouse model of DS, our group has demonstrated that supplementing the maternal diet with additional choline (4-5x standard levels) during pregnancy and lactation improves spatial cognition, attention, and emotion regulation in the adult offspring. The behavioral benefits were associated with a rescue of septohippocampal circuit atrophy. These results have been replicated across a series of independent studies, although the magnitude of the cognitive benefit has varied. We hypothesized that this was due, at least in part, to differences in the age of the subjects at the time of testing. Here, we present new data which compares the effects of MCS on attentional function of adult Ts65Dn offspring which began testing at two different ages (6 vs. 12 months of age). These data replicate and extend results of our previous reports, showing a clear pattern indicating that MCS has beneficial effects in Ts65Dn offspring throughout life, but that the magnitude of the benefit (relative to non-supplemented offspring) diminishes with aging, possibly due to the onset of Alzheimer’s disease-like neuropathology. In light of growing evidence that increased maternal choline intake during pregnancy is beneficial to the cognitive and affective functioning of all offspring (e.g., normal developing and DS), the addition of this nutrient to a prenatal vitamin regimen would be predicted to have population-wide benefits and provide an early intervention for DS fetuses, notably including babies born to mothers unaware that they are carrying a DS fetus.